Procalcitonin as a prognostic marker for outcomes in post-cardiac arrest patients: A systematic review and meta-analysis. (May 2019) - Shin, Hyungoo; Kim, Jae Guk; Kim, Wonhee; Lim, Tae Ho; Jang, Bo-Hyoung; Cho, Youngsuk; Choi, Kyu-Sun; Ahn, Chiwon; Lee, Juncheol; Na, Min Kyun
Abstract: Aim: This study aimed to seek evidence for the usefulness of the procalcitonin as a prognostic blood biomarker for outcomes in post-cardiac arrest patients. Methods: We systematically searched MEDLINE, EMBASE, and the Cochrane Library (search date: 8 January, 2019). Studies on patients who experienced return of spontaneous circulation, who had out of hospital cardiac arrest and had their level of procalcitonin measured and outcomes assessed at and after hospital discharge, were included. We additionally performed subgroup analyses for confounding factors affecting patients' outcomes. To assess the risk of bias of each included study, the Quality in Prognosis Studies tool was used. Results: A total of 1065 patients from 10 studies were finally included. Elevated procalcitonin level during hospital admission (at 0–24 h) was associated with in-hospital mortality (standardized mean difference (SMD) 0.64, 95% confidence interval (CI) 0.33–0.95, I 2 = 26%). The elevation of procalcitonin level (at 0–48 h) was also associated with poor neurologic outcomes (at 0–24 h, SMD 0.61; 95% CI 0.44–0.79, I 2 = 0%; at 24–48 h, SMD 0.58, 95% CI 0.35–0.82, I 2 = 0%) as well as at 1–6 months (at 24–48 h, SMD 0.62; 95% CI 0.36–0.88, I 2 = 0%). Conclusions: Overall, the findings suggested that an elevated procalcitonin level measured at 0–48 h of post-cardiac arrest syndrome was associated with poor outcomes.